Nonlinear Dissipative Systems in Vicinity of Internal and Forced Resonances - Plaksiy, Katerina; Mikhlin, Yuri V. (Institute of Mechani cs and Mechatronics, Technical University of Vienna, 2014)
Free and forced dynamics of some nonlinear dissipative systems in vicinity of internal resonance is considered. A reduced system with respect to the system energy, an arctangent of the vibration amplitudes ratio, and the phase difference is used in the analysis.
Keywords: energy transfer and localization; nonlinear systems; vibration amplitudes; dissipative systems; передача та локалізація енергії; нелінійні системи; амплітуди вібрації; дисипативні системи